KAJIAN NORMATIF TERHADAP KEJAHATAN PEMALSUAN UANG DI INDONESIA - H.M. IKHWAN RAYS (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2019)
Crime of counterfeiting currency nowadays increasingly rampant in large scale and very worried about where most major impact inflicted by the crimes of counterfeiting currency is the monetary condition and can threaten the national economy. In terms of its impact on the interests of the State, the crime of counterfeiting money destroy public confidence towards its own currency. This research aims to find out how the provisions of the law against the crime of counterfeiting money rupiah and distribution in positive law Indonesia as well as other forms of prevention in order to prevent the occurrence of counterfeit money in Indonesia. To find out the purpose of this research is then referred to using the pendekatanYuridis method or the way in which the Normative used in legal research conducted by way of researching the existing library materials. Crime of counterfeiting coins in positive law in Indonesia set forth in KUHPidana of Article 244 of the CRIMINAL CODE up to 252 of the CRIMINAL CODE, and more specifically set forth in Act No.: 7 year 2011 about the currency in which the provisions of criminal law that are enshrined in article 33 to article 41. Are these forms of prevention include: giving to the community's understanding of how the characteristics of genuine money with fake money, the role of banking and trade/cash handlers, Request clarification, information research results and follow-up over the the money that doubt its authenticity and the report on the discovery of counterfeit money by foreign banks